Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0091187
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage pH Control Strategy Based on the pH Preference of Acetoin Reductase Regulates Acetoin and 2,3-Butanediol Distribution in Bacillus subtilis

Abstract: Acetoin reductase/2,3-butanediol dehydrogenase (AR/BDH), which catalyzes the interconversion between acetoin and 2,3-butanediol, plays an important role in distribution of the products pools. This work characterized the Bacillus subtilis AR/BDH for the first time. The enzyme showed very different pH preferences of pH 6.5 for reduction and pH 8.5 for oxidation. Based on these above results, a two-stage pH control strategy was optimized for acetoin production, in which the pH was controlled at 6.5 for quickly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Many bacterial strains like Enterobacter aerogenes, Serratia marcescens, Paenibacillus polymyxa, or Bacillus subtilis can produce acetoin (Xiao and Lu, 2014). Using Bacillus, Zhang et al (2014Zhang et al ( , 2016 reported yields of 68.5%-83.5% depending on the substrate and the genetic background of the strains. Bacillus subtilis is by the Food and Drug Administration listed as a "generally regarded as safe" strain (Xiao and Lu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many bacterial strains like Enterobacter aerogenes, Serratia marcescens, Paenibacillus polymyxa, or Bacillus subtilis can produce acetoin (Xiao and Lu, 2014). Using Bacillus, Zhang et al (2014Zhang et al ( , 2016 reported yields of 68.5%-83.5% depending on the substrate and the genetic background of the strains. Bacillus subtilis is by the Food and Drug Administration listed as a "generally regarded as safe" strain (Xiao and Lu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the commercial acetoin is a racemic mixture which is mainly produced by chemical way, while the biological product is highly enantioselective. Therefore, acetoin fermentation has attracted much attention in recent years, and many exciting results through strain screening and enhancement, fermentation strategies on pH control and aeration control have been achieved to increase acetoin production [1,2], and the highest acetoin concentration reached 73.6 g/l by an engineered Bacillus subtilis strain when glucose was used as carbon source [3]. Direct production of acetoin from 2,3-butanediol was also an efficient way and the acetoin concentration reached 89.2 g/l by Gluconobacter oxydans DSM 2003 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The acetoin concentration was generally around 40 g/l obtained by the wild type of Bacillus strains [7][8][9] and the highest could reach 51.2 g/l by a native strain of B. amyloliquefaciens FMME044 [10]. After mutagenesis the concentration of acetoin was increased to more than 50 g/l [3,[11][12][13][14]. The production ability and culture conditions of strains which were generally recognized as safe (GRAS) were compared ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…These results confirmed the extracellular cellulase activity of the bacterial strain. [61]. RCS was estimated to have 8.98 g/L crude proteins, and it also contained all the essential amino acids for bacterial growth, and some -and -amino-butyric acid (AIB, GABA) (see Figure S3 in Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%